Pengaruh Konflik Peran, Ambiguitas Peran, dan Kelebihan Peran Terhadap Kualitas Audit - Reynaldo Savero; Agus Munandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to examine whether role conflict, role ambiguity and role excess have an influence on auditor quality. This study uses a survey approach in the form of a questionnaire filled out by 67 auditors in Jakarta as respondents. The data in this study were processed using SPSS 25 For Windows software. The hypothesis in this study was tested using multiple regression tests, T tests and F tests. The results in this study indicate that role conflict, role ambiguity and role overload have a significant effect on audit quality.